Peningkatan Pemahaman Ibu Hamil tentang Bahaya KEK melalui Edukasi Gizi Seimbang di Ohoi Ohoitel Kota Tual - Agnes Batmomolin; Notesya Astri Amanupunnyo (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Nutrition is balanced with the adequacy of nutrients and energy is an important key for the health of the mother and fetus during pregnancy. malnutrition and energy during pregnancy can have a bad impact on the health of pregnant women, as well as fetal safety. This community service activity aims is to provide understanding of pregnant women about the importance of balanced nutrition during pregnancy and the dangers of lack of chronic energy for health of the mother and fetus. Ohoi Ohoitel is one of Ohoi in the city of Tual which has many pregnant women with lack of protein energy (23.5% of the total pregnant women in Ohoi). The Community Service Team through Collaboration with Ohoitahit Health Center, Ohoi Ohoitel Health Cadre and Ohoi Ohoitel's head provided health education to pregnant women. The focus of health education emphasizes the selection of local food ingredients produced by the local community to be processed and served to meet the nutritional needs of pregnant women and families. Health education takes place well, and there are 90% increased understanding of pregnant women. The follow -up of the community service activities will be carried out by Cadres and Ohoitahit Health Center.